Beneficial Effect of Alkaloids From Sophora alopecuroides L. on CUMS-Induced Depression Model Mice via Modulating Gut Microbiota - Zhang, Ming; Li, Aoqiang; Yang, Qifang; Li, Jingyi; Wang, Lihua; Liu, Xiuxian; Huang, Yanxin; Liu, Lei (Frontiers in Cellular and Infection Microbiology, 2021)
It was recently shown that the gut microbiota of both depression patients and depression model animals is significantly altered, suggesting that gut microbes are closely related to depression. Here, we investigated the effects of Sophora alopecuroides L.-derived alkaloids on the gut microbiota of mice with depression-like behaviors. We first established a mouse model of depression via chronic unpredictable mild stress (CUMS) and detected changes in depression-like behaviors and depression-related indicators. Simultaneously, 16S rRNA sequencing was performed to investigate gut microbiota changes. Sophora alopecuroides L.-derived alkaloids improved depression-like behaviors and depression-related indicators in mice. The alkaloids decreased the gut microbiota diversity of CUMS mice and depleted intestinal differentially abundant "harmful" microbiota genera. Spearman analysis showed that there is a certain correlation between the differential microbiota (Lactobacillus, Helicobacter, Oscillospira, Odoribacter, Mucispirillum, Ruminococcus), depression-like behaviors, and depression-related indicators. Combined with the predictive analysis of gut microbiota function, these results indicate that alkaloids improve depression in mice through modulating gut microbiota.